Life Expectancy with and Without Cognitive Impairment Among Chilean Older Adults: Results of the National Survey of Health 2003 2009 and 2016 - Moreno-Herrera, F (BioMed Central Ltd., 2019)
Background: Chile has one of the highest life expectancies within Latin American. This is the first study to determine health expectancies in older populations in Chile, considering cognitive status as a health indicator. Methods: We estimated prevalence of cognitive decline among people aged 60 years and over based on the Mini-mental State Examination and the Pfeffer Functional Activities Questionnaire, with data from the National Survey of Health (2003, 2009, 2016). Life expectancy free of cognitive impairment was calculated using the Sullivan method. Results: At age 60, life expectancy free of cognitive impairment was more than 3 years longer for women, compared to men of the same age. Life expectancy free from cognitive impairment was higher for both men and women aged 60 in 2016 when compared to 2003 (2.1 and 2 years higher, respectively). Conclusions: Longer life expectancy in women was accompanied by more years free of cognitive impairment. Men expected to live a similar proportion of years free of cognitive impairment, compared to women. Common and standardised assessments of health status of older people should be adopted in Latin American studies, to allow for time-trend analyses and international comparisons. © 2019 The Author(s).